A preliminary study on tourist willingness to pay for marine safety improvements in Nusa Penida - Habibah Siti Nur; Rahman Ari; Lee Chun-Hung (BIO Web of Conferences)
This study evaluates the willingness to pay (WTP) among tourists for safety improvements in Nusa Penida, Indonesia, utilizing the contingent valuation method (CVM). The research aimed to quantify the economic value that tourists place on enhanced safety measures and to identify demographic factors influencing their WTP. Data were collected through a structured questionnaire distributed to a diverse group of tourists. The results revealed a clear preference for moderate safety investment, with a significant drop in WTP as the proposed enhancements’ costs increased. Chi-square tests conducted to explore the relationship between WTP and demographic variables such as gender, income, education level, age, and marital status. The results showed there was no significant associations between them, suggesting that safety is a universally valued attribute among tourists irrespective of their demographic backgrounds. These findings provide crucial insights for local policymakers and tourism managers, indicating that safety improvements have broad support and can be implemented universally without demographic segmentation. The study highlights the importance of integrating tourist perspectives into safety enhancement strategies, which not only increases the likelihood of their acceptance but also contributes to the sustainable development of the tourist management in Nusa Penida, Indonesia.